Role of Propriospinal Neurons in Control of Respiratory Muscles and Recovery of Breathing Following Injury - Jensen, Victoria N.; Alilain, Warren J.; Crone, Steven A. (Frontiers in Systems Neuroscience, 2020)
Respiratory motor failure is the leading cause of death in spinal cord injury. Cervical injuries disrupt connections between brainstem neurons that are the primary source of excitatory drive to respiratory motor neurons in the spinal cord and their targets. In addition to direct connections from bulbospinal neurons, respiratory motor neurons also receive excitatory and inhibitory inputs from spinal interneurons, yet their role in the control of breathing is often overlooked. In this review, we will present evidence that spinal interneurons play important roles in patterning muscle activity for breathing. These roles likely include shaping the pattern of motor output, mediating responses to afferent feedback, coordinating the activity of different respiratory muscles, and matching respiratory muscle recruitment to behavioral or physiological demands. We will discuss these roles, as well as recent studies that have highlighted the importance of propriospinal neurons for recovery of respiratory muscle function following SCI. We propose that spinal respiratory circuits share important characteristics with locomotor central pattern generator circuits and discuss the implications for neural plasticity and repair. Finally, we will discuss the potential of approaches targeting propriospinal circuits to improve recovery of breathing and rescue patients with SCI from ventilator dependence.